Peranan Dokter Ahli Kandungan Dalam Pembuktian Perkara Aborsi(Studi Putusan Pengadilan Negeri Klaten) - Denny, Denny, Hartanto, S.H., M.Hum (2016)
The purpose of this study was to analyze the consideration of the judge in the settlement of abortion in Klaten District Court and the role of gynecologists in proving the case of abortion. This research includes normative legal research. Research conducted in the Klaten District Court. Source data using secondary data. Data were analyzed using qualitative analysis. The results showed that: First, the deliberations of the judge in the settlement of abortion in the District Court of Klaten is of legal considerations, consideration of fact of the trial, and sociological considerations; Second, the role of gynecologists in proving the case of abortion there are 2 of a post mortem maker and as an expert witness. Doctors as a maker of a post mortem be used as a guide or guidelines and evidence in investigate, prosecute and adjudicate on civil and criminal cases. Doctor as an expert witness: giving a description of the theory / hypothesis, to provide information about an object, and the obligation of the doctor as an expert witness.